Evaluation of the Needs of Ferry Boats on the Tanjung Kalian – Tanjung Api-Api Bangka Belitung Province - Doharman Lumban Tungkup; Febriansyah Febriansyah; Devia Amanda (IWJ : Inland Waterways Journal, 2021)
Tanjung Kalian Ferry Port is a ferry port that connects Sumatra Island and Bangka Island which has a distance of 30 miles. The Tanjung Kalian – Tanjung Api-Api route has 13 (thirteen) ships that operate for a travel time of 240 minutes or 4 hours. High productivity of passengers and vehicles on the Tanjung Kalian – Tanjung Api-Api route which causes the ship's carrying capacity to exceed the provided capacity, resulting in load accumulation. The method of analysis of the carrying capacity on the ship uses the analysis of the daily average load factor calculation. The primary data used is a survey of productivity data for departures and arrivals for 15 days from April 21 – May 5, 2021, survey data for ship sailing times, and survey data for ship layover time for the Tanjung Kalian – Tanjung Api-Api route. By looking at the increasing productivity of passengers and vehicles at the Tanjung Kalian Ferry Port, there is an increase in the needs of service users that must be met, including the frequency of ships and the number of ships operating. In accordance with the results of the analysis, Tanjung Kalian Ferry Port must increase the frequency of ships to 19 trips/day. This is used to overcome the number of service users who are not transported.